Recognizing Statistical Problems in Reports of Clinical Trials: a Readers' Aid: Part 33 of a series on evaluation of scientific publications. - Suling, A.; Großhennig, A. (Deutsches Ärzteblatt International, 2024)
Background: Readers of clinical trial reports should be able to critically evaluate the design, results, and conclusions of the trial. There are internationally accepted guidelines that define methodological standards for trial planning, statistical methods, and the display and interpretation of the results. Publications may nonetheless contain erroneous findings and interpretations. Methods: Statistical errors can arise in the planning of the trial, the analysis and display of the results, as well as in the interpretation of p-values and treatment effects in experimental and observational clinical trials. A useful aid for readers of medical publications should include a description of the potential statistical problems without complex theoretical background information. With this aim, we discuss certain major types of statistical error that the reader should be familiar with in order to be able to interpret the conclusions of these publications more easily. Results: Statistical errors can already arise at an early stage through the choice of the wrong question to be addressed or the wrong population to be analyzed; such errors will inevitably have consequences. Before the start of any clinical trial, a primary endpoint must be defined, the sample size must be calculated, and the trial must be appropriately registered (among other requirements). With regard to the analysis, readers should for example take into account whether a statistical analysis plan with an intention-to-treat analysis existed for the study in question. They must be able to recognize erroneous methods of displaying and comparing data, confounding, as well as incorrect interpretations of p-values, and should take these problems into account when interpreting the findings. The problem of invalid causal inferences is not restricted to observational studies. Conclusions: Statistical errors do, indeed, arise. They should be detected as early as possible in various test instances. Nonetheless, readers should be able to judge independently whether the published clinical trial reflects meticulous and correct trial planning, appropriate display of the trial's results, and a proper, reasoned interpretation of the findings. The published checklists are a good aid for this purpose.